Governmental Skills: The Spirit in the Old Testament - Christar Arstilo Rumbay (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2021)
Pneumatology and its significance to the Old Testament have been discussed throughout the years. Indeed, the Old Testament is the ground knowledge of the whole scripture, while pneumatology is the heart of Christian theology due to its connection to the trinity doctrine. This chapter attempts to explore the activities of the Spirit concerning her governmental skills in the Hebrews bible. A systematic theology approach leads this essay to gain knowledge on how the Spirit testifies her competence in governmental works. As a result, the nature of the Spirit’s governmental work in the Old Testament relates to cosmological sense, leadership-administrative duties, and war strategy.